Understanding the Prohibition of Interfaith Marriage in Islamic Teachings: A Semiotic Analysis Of Q.S. Al-Baqarah (2):221 Using Ferdinand de Saussure's Approach - Memed Khumaedi; Haeruddin; Jusalim Sammak; H. Abdul Hafid; Ilham Azis (International Journal of Health, Economics, and Social Sciences (IJHESS), 2024)
This research aims to understand the prohibition of interfaith marriage in Islamic teachings through the analysis of the sacred texts of the Quran and Hadith using Ferdinand de Saussure's semiotic approach. Saussure's semiotic approach allows us to understand the signs and meanings contained in the verses and hadiths regarding interfaith marriage. In Islam, the prohibition of interfaith marriage is found in Surah Al-Baqarah (2):221. The research methodology used involves literature research and findings show that literally, this verse prohibits Muslims from marrying non-Muslims, including the people of the book (those who have sacred books like Jews and Christians) and polytheists (idol worshippers). However, the understanding of this verse provides tolerance with certain conditions. Muslim men are allowed to marry people of the book with the intention of inviting their partners to embrace Islam, while Muslim women are not allowed to marry non-Muslim men. The prohibition also includes Muslim men marrying polytheistic women, including idol worshippers, atheists, fire worshippers, apostates, and followers of libertine sects. In this research, the author used the literature research method to analyze relevant texts. Saussure's semiotic analysis helps in understanding the linguistic signs and meanings contained in these texts. Thus, this research provides a deeper understanding of the prohibition of interfaith marriage in the context of Islamic religion. The results of this research not only enhance religious understanding but also provide a basis for further research in this field. By using the semiotic approach, we can better understand the signification and meanings contained in religious texts and how it affects the religious practices of Muslims regarding interfaith marriage. Ultimately, this research shows that the prohibition of interfaith marriage in Islam has a strong theological foundation and requires careful understanding of the sacred texts. Saussure's semiotic analysis provides deeper insights into the meanings and signification contained in these texts, thus providing a richer understanding in the religious context. Therefore, this writing is not only aimed at enhancing religious understanding but also offers a foundation for further research in this field.